To be a feminist in (tourism) academia. Issue 4 (2nd October 2017) - Munar, Ana María
Abstract: This study explores what it means to be a feminist in (tourism) academia. Different understandings of feminist identity and their ethical and political dimensions are examined using the method of the vignette. This technique is applied as an autoethnographic and narrative tool that facilitates the exploration of feminism from multiple viewpoints. Three characters, Sheryl-Ana, Gloria-Ana, and Gaga-Ana, are presented, drawing inspiration from the literature and my own life experiences, research and activism in tourism academia. These narratives are followed by a discussion on multiple ways of doing academic feminism and demonstrating our capacities for political engagement.